2013
DOI: 10.4028/www.scientific.net/amm.388.280
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation in Turbulent Swirl-Stabilized Flame: Effect of Hydrogen Enrichment

Abstract: A set of numerical simulations were conducted to estimate the change in entropy generation in swirl stabilized CH4/air flames due to H2 addition to the fuel. A robust finite volume computational model solving the Reynolds Averaged Navier Stokes with a first order turbulence closure and laminar flamelet combustion model was used to compute the flow and energy fields in the flame. Hydrogen enrichment resulted in an increase in the entropy generation rate of the flame. Such increase was attributed to the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Another approach (e.g. [32][33][34]) is simply to neglect all other contributions but viscous and conduction. For the present cases, the effects of this can be seen by comparing the conduction component, Figs.…”
Section: Simplified Models For Entropy Generationmentioning
confidence: 99%
“…Another approach (e.g. [32][33][34]) is simply to neglect all other contributions but viscous and conduction. For the present cases, the effects of this can be seen by comparing the conduction component, Figs.…”
Section: Simplified Models For Entropy Generationmentioning
confidence: 99%
“…The entropy generated due to mass transfer alone increased slightly with increase in air inlet temperature whereas the entropy generation due to heat transfer and chemical reactions decreased with air preheat. Saqr and Wahid [22] studied the effect of hydrogen addition on the entropy generation in swirl stabilized methane flames. It was found that the rate of entropy generation increased with the addition of hydrogen to methane diffusion flames due to the irreversibility caused by heat transfer.…”
Section: Introductionmentioning
confidence: 99%